ANALYSIS OF SUCCESSFUL EXAMPLES OF CRITICAL DISCUSSIONS AND DEBATES - Khaydarova Nigora; Madaminjonova Mubina (TADQIQOTLAR, 2025)
Abstract: This article explores successful examples of critical discussions and debates in various spheres- academic, political, and media. It examines both historical and  contemporary  formats  of  debates  and  identifies  key  factors  of  effectiveness, including logical structure, strong argumentation, respect for opponents, and a cultured speech style. The article highlights the importance of critical discussions in shaping analytical thinking and democratic culture.